2019
DOI: 10.3390/w11091842
|View full text |Cite
|
Sign up to set email alerts
|

Application of Stable Isotopes of Water to Study Coupled Submarine Groundwater Discharge and Nutrient Delivery

Abstract: Submarine groundwater discharge (SGD)—including terrestrial freshwater, density-driven flow at the saltwater–freshwater interface, and benthic exchange—can deliver nutrients to coastal areas, generating a negative effect in the quality of marine water bodies. It is recognized that water stable isotopes (18O and 2H) can be helpful tracers to identify different flow paths and origins of water. Here, we show that they can be also applied when assessing sources of nutrients to coastal areas. A field site near a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 68 publications
(91 reference statements)
1
12
0
Order By: Relevance
“…The majority of the contributions [3,5,[8][9][10][11][15][16][17][19][20][21][22][23] focus on the interactions between rivers or streams and groundwater. Three studies [6,13,14] investigate the interactions between lakes and groundwater, while two studies [4,18] deal with the exchange between groundwater and oceanic water. Two additional contributions [7,12] show the relevance of groundwater exchange processes in wetlands.…”
Section: Overview Of the Special Issue Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the contributions [3,5,[8][9][10][11][15][16][17][19][20][21][22][23] focus on the interactions between rivers or streams and groundwater. Three studies [6,13,14] investigate the interactions between lakes and groundwater, while two studies [4,18] deal with the exchange between groundwater and oceanic water. Two additional contributions [7,12] show the relevance of groundwater exchange processes in wetlands.…”
Section: Overview Of the Special Issue Contributionsmentioning
confidence: 99%
“…Tirado-Conde et al [18] compare the results of traditional seepage meter measurements with several analytical approaches of vertical sediment temperature profiles in a lagoon in Denmark. Duque et al [4] applied stable isotopes of water to delineate flow paths and the origin of water in a coastal aquifer. This enabled them to draw valuable conclusions on nutrient transport and their fate along the vector from freshwater to saline environments.…”
Section: Groundwater-ocean Interactionsmentioning
confidence: 99%
“…Terrestrial groundwater is substantially more depleted in the heavier isotopes than seawater (Gat, 1996;Hoefs, 2018) and contains further information about the integrated meteorological conditions in the recharge area. Therefore, water isotopes are widely used in studies of SGD or STE (e.g., Burnett et al, 2006;Povinec et al, 2011;Rocha et al, 2016;Oehler et al, 2017;Duque et al, 2019). Time series can reveal the variability of terrestrial groundwater inputs on different time scales, particularly in dynamic karst STEs.…”
Section: Approaches To Assessing Ste Processes At the Regional Scale Geochemical Tracersmentioning
confidence: 99%
“…As part of coastal environments, lagoons are always located in lowland areas where nutrient inputs from the hinterland are often high, and thus lagoons often suffer from eutrophication (Coluccio et al, 2021). Besides riverine inputs, it has been shown that lagoons and coastal water bodies receive large amounts of nutrients through submarine groundwater discharge (SGD) (Corbett et al, 1999;Li et al, 1999;Ji et al, 2013;Rodellas et al, 2015;Duque et al, 2019). The groundwater component discharging into lagoons can vary from minor contributions (Menció et al, 2017) to contributions up to 90% (Sadat-Noori et al, 2016) with seasonal variations (Menció et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Density-driven hydrodynamic conditions in the subsurface of lagoons can be generally expected to be quite similar to coastal systems connected with the adjacent sea, yet the reduction or absence of diurnal tides potentially make the subsurface flow, and its linked subsurface nutrient cycling, different for coastal lagoon aquifers. Coastal subterranean groundwater flow dynamics and SGD are influenced by multiple factors, varying in temporal and spatial scales and hence, creating a complex subsurface flow system (Robinson et al, 2006;Heiss and Michael, 2014;Duque et al, 2019;Meyer et al, 2019). The spatial extension of the saltwater wedge and exchange fluxes between salt and freshwater depend on diffusion and dispersion processes linked to hydrogeological and chemical settings.…”
Section: Introductionmentioning
confidence: 99%